Implementation Of Tabu Search Algorithm to Solve the Capacitated Vehicle Routing Problem (CVRP) In Medicine Distribution Route - Abdul Aziz, Riyan; Moch. Hari Purwidiantoro; Syams Kurniawan Hidayat; Muhammad Setiyawan (Politeknik Aceh, 2025)
One of the optimization issues is the Vehicle Routing Problem (VRP). VRP can consider distance alone or take into account other factors such as traffic congestion, road quality, and obstacles to serve multiple agents according to their requests. The Capacitated Vehicle Routing Problem (CVRP), which adds vehicle capacity constraints, is a variant of VRP. This paper aims to explain the construction of a CVRP model for the problem of drug distribution routes from a depot to several pharmacies. An approach called Tabu Search is proposed to overcome these optimization challenges. The main objective of this method is to stop the iterative search for solutions that have already been sought. In this study, the travel route for the example of a PT. XYZ Salesman was constructed using the Tabu Search approach. The results obtained a minimum travel distance of 27.9 km and a minimum travel time of 35.2 minutes, with a maximum delivery quantity of 63 boxes.